Комп’ютерне моделювання термінальних вантажних перевезень - Прокудін, Г.С.; Дехтярук, М.Т. (Моделювання та інформаційні технології, 2009)
It is shown, that the computer design is the effective method of research of organization of transport process. By means the system of the object-oriented programming Delphi the developed simulation model of the custom terminal system within the framework of theory of mass service. The developed system of design of freight transportations on a custom terminal, during conducting of experiments with the mathematical model of object, possibility gives to conduct the analysis and optimization of the modes of operations of custom terminal network.